Étude des conceptions du poids d’un corps chez les apprenants des classes de troisième (13-15 ans) de l’enseignement secondaire général camerounais - Jérémie AWOMO ATEBA; Andrienne Victorine MANTO MBA; Nicole Aimée AMBOMO; AYINA BOUNI (Revue Hybrides)
The weight is a fundamental concept in physics. Its early handling in everyday life induces enormous modelling difficulties in learners, and these persist even after teaching. In the present study, we set out to determine the conceptions of Cameroonian pupils in the third year of general secondary education (aged 13-15) about the concept of the weight. Successive exploration of two avenues: an institutional avenue (analysis of the official textbook) and an epistemological avenue enabled us to construct a questionnaire consisting of 11 open and semi-open questions. It was administered to 95 learners in third-year classes who had been taught about the weight a year earlier. The data collected were analysed according to the modelling scheme proposed by Martinand (1996). The results showed that even after instruction, most of the learners still had an Aristotelian conception of the fall of bodies to earth. They still confuse the concepts of weight and mass and have difficulty representing the weight in a spatial reference frame. Learners' reasoning is therefore based almost entirely on phenomenography (Martinand, 1996). For a better conceptualisation of the weight concept, teachers should use the conceptions identified in this work to propose activities in which learners construct weight from the interpretation of everyday phenomena.